Antigenic Complementarity in the Origins of Autoimmunity: A General Theory Illustrated With a Case Study of Idiopathic Thrombocytopenia Purpura. Issue 1 (2006) - Root-Bernstein, Robert; Couturier, Jacob
Abstract : We describe a novel, testable theory of autoimmunity, outline novel predictions made by the theory, and illustrate its application to unravelling the possible causes of idiopathic thrombocytopenia purpura (ITP). Pairs of stereochemically complementary antigens induce complementary immune responses (antibody or T-cell) that create loss of regulation and civil war within the immune system itself. Antibodies attack antibodies creating circulating immune complexes; T-cells attack T-cells creating perivascular cuffing. This immunological civil war abrogates the self-nonself distinction. If at least one of the complementary antigens mimics a self antigen, then this unregulated immune response will target host tissues as well. Data demonstrating that complementary antigens are found in some animal models of autoimmunity and may be present in various human diseases, especially ITP, are reviewed. Specific mechanisms for preventing autoimmunity or suppressing existing autoimmunity are derived from the theory, and critical tests proposed. Finally, we argue that Koch's postulates are inadequate for establishing disease causation for multiple-antigen diseases and discuss the possibility that current research has failed to elucidate the causes of human autoimmune diseases because we are using the wrong criteria.